LncRNA XIST Reduces Myocardial Injury in Myocarditis by Targeting the miR-140-3p/RIPK1 Axis - Zhou, Jiaxin (Journal of Neonatal Surgery, 2025)
Introduction: Myocarditis, an inflammatory disease of the myocardium, can lead to serious cardiac conditions such as arrhythmias, systolic and diastolic dysfunction, and, in severe cases, sudden cardiac death. The condition has various etiologies, including immune response, bacterial, and viral infections, but its pathophysiology is not yet fully understood, and treatment remains largely symptomatic. Long non-coding RNAs (lncRNAs), particularly X inactivation-specific transcript (XIST), have emerged as significant regulators in cardiac diseases. However, XIST's role in myocarditis has not been fully elucidated. This study investigates XIST's protective effects on primary rat cardiomyocytes during lipopolysaccharide-induced myocarditis and explores its underlying molecular mechanism. Materials and Methods: Rat primary cardiomyocytes were treated with XIST-loaded lentiviruses and exposed to lipopolysaccharide (LPS) to induce myocarditis. Quantitative PCR was used to determine XIST expression, while MTS, ELISA, flow cytometry, and Western blot assays evaluated cell viability, cytokine levels, apoptosis, and protein expression. Bioinformatics analysis and a dual-luciferase reporter assay examined the interaction between XIST and miR-140-3p. Results: Compared with the control group, XIST overexpression in cardiomyocytes significantly increased cell viability, reduced IL-1β and TNF-α secretion, and decreased apoptosis. Bioinformatics and dual-luciferase reporter assay confirmed miR-140-3p as a direct target of XIST, suggesting XIST regulates cardiomyocyte survival through miR-140-3p interaction. Conclusion: XIST exerts a protective role against LPS-induced cardiomyocyte injury in myocarditis, potentially by targeting miR-140-3p. These findings provide new insights into lncRNA-based therapeutic strategies for myocarditis.